2009
DOI: 10.1128/iai.01485-08
|View full text |Cite
|
Sign up to set email alerts
|

Francisella tularensisPhagosomal Escape Does Not Require Acidification of the Phagosome

Abstract: Following uptake, Francisella tularensis enters a phagosome that acquires limited amounts of lysosomeassociated membrane glycoproteins and does not acquire cathepsin D or markers of secondary lysosomes. With additional time after uptake, F. tularensis disrupts its phagosomal membrane and escapes into the cytoplasm. To assess the role of phagosome acidification in phagosome escape, we followed acidification using the vital stain LysoTracker red and acquisition of the proton vacuolar ATPase (vATPase) using immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 40 publications
1
66
0
Order By: Relevance
“…Although the ultrastructural appearance of the bacteria in this study (Fig. 3) is similar to some specimens of F. tularensis in host cells depicted by Clemens et al (2009) andLian (2016), they look different from the electron micrographs presented for F. halioticida by Brevik et al (2011). Also, the bacteria measurements re corded in this study via TEM fall within the size range of Francisella spp.…”
Section: Discussionmentioning
confidence: 50%
“…Although the ultrastructural appearance of the bacteria in this study (Fig. 3) is similar to some specimens of F. tularensis in host cells depicted by Clemens et al (2009) andLian (2016), they look different from the electron micrographs presented for F. halioticida by Brevik et al (2011). Also, the bacteria measurements re corded in this study via TEM fall within the size range of Francisella spp.…”
Section: Discussionmentioning
confidence: 50%
“…It is interesting to note that acidification is actually required for the rapid phagosomal escape of the intracellular pathogen Listeria monocytogenes (27). Studies with Francisella have shown a brief acidification of the FCP that is dependent on the route of uptake, although there has been debate about whether this step is required for rapid escape and about its effect on the outcome of infection, as detailed below (49,52,53,194).…”
Section: Phagosomal Acidificationmentioning
confidence: 99%
“…Additionally, the authors found that the maturing FCP does not acquire high levels of the acid hydrolase cathepsin D, which is a cellular marker of acidification, or the endosomal-lysosomal markers CD63, LAMP1, and LAMP2, which are cellular markers of phagosomal maturation (52,53). In contrast to the previously mentioned work using unopsonized bacteria, BFA did not significantly delay infection kinetics in these experiments using serum-opsonized bacteria (53). These data demonstrate that acidification of the FCP is not required for escape and replication of unopsonized or serum-opsonized Francisella but is required for rapid escape of unopsonized Francisella.…”
Section: Phagosomal Acidificationmentioning
confidence: 99%
See 1 more Smart Citation
“…It also remains controversial whether exposure to acidic pH is necessary and/or sufficient for F. tularensis egress from the phagosome. Studies conducted by Clemens et al using THP1 cells (a human macrophage-like cell line) or primary macrophages derived from peripheral blood monocytes have demonstrated that FCVs harboring LVS or type A F. tularensis become only minimally acidified (pH of 6.7) and acquire limited amounts of the proton vacuolar ATPase (34,35). Additionally, use of the proton pump inhibitor bafilomycin A prior to infection of these macrophage types with F. tularensis strains does not alter the efficiency of F. tularensis phagosomal escape (34).…”
Section: Intracellular Life Cycle Of F Tularensis In Phagocytic Cellsmentioning
confidence: 99%